OPPORTUNITIES FOR INCREASING THE COMPETITIVENESS OF TOURIST ENTERPRISES IN UZBEKISTAN (ResearchJet Journal of Analysis and Inventions, 2023)
This article describes the competitiveness of the services of tourist companies, a system of factors that ensure consumer convenience, the efficiency of expenses incurred in tourism, and the abundance of profitability from the service.